PENINGKATAN KOMPETENSI GURU TK/PAUD MELALUI KEGIATAN UNPLUGGED CODING DALAM PEMBELAJARAN DEEP LEARNING - Sonjaya, Trisna; Hendrarso, Panji; Solihin, Ihin; Priyanti, Nita (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
TK Kartika XIX 38 Pandeglang is located at Jl. Letnan Bolang No. 9, Pandeglang Village, Pandeglang District, Pandeglang Regency, Banten Province. The current learning problems of TK Kartika XIX 38 Pandeglang students are: (1) teachers do not have Unplugged Coding textbooks; (2) teachers do not have learning guidebooks in Deep Learning; and (3) workshops on compiling unplugged coding teaching materials have not been implemented. The solutions offered are: (1) Compiling unplugged coding teaching materials for students systematically; (2) compiling learning guidebooks in deep learning based on curriculum references and basic competencies; and (3) implementing workshop activities on compiling deep learning by learning guidebooks. The method offered to address partner problems in community service programs is by using the ABCD (Asset-Based Community Development) method to improve teacher competency through workshops and accompanying unplugged coding learning activities at TK Kartika XIX 38 Pandeglang. Analysis Stage (A) the implementing team consisting of lecturers and students conducted a survey, identified partner problems and collected data. Preparation Stage (B) carried out socialization and focus group discussions (FDG) with partners, prepared a workshop schedule, prepared unplugged coding learning activities and prepared activity equipment with partners. Implementation Stage (C) the implementing team started of deep learning workshop activities, mentored teachers in preparing learning tools and accompanied unplugged coding learning activities together with partners. Evaluation Stage (D) PkM activity program was carried out by the chairman and all members, to provide solutions to problems faced by partners. The results of community service carried out at TK Kartika XIX 38 Pandeglang for eight months, there was an increase in teacher competence in the deep learning of learning process, a positive impact after the unplugged coding workshop activity, namely teachers can use teaching materials and learning tools, and deep learning can be implemented effectively and efficiently to achieve learning objectives